Metabolic labeling of HIV-1 envelope glycoprotein gp120 to elucidate the effect of gp120 glycosylation on antigen uptake - Sun, Lina (J Biol Chem, 2018)
The glycan shield on the envelope glycoprotein gp120 of HIV-1 has drawn immense attention as a vulnerable site for broadly neutralizing antibodies and for its significant impact on host adaptive immune response to HIV-1. Glycosylation sites and glycan composition/structure at each site on gp120 along with the interactions of gp120 glycan shield with broadly neutralizing antibodies have been extensively studied. However, a method for directly and selectively tracking gp120 glycans has been lacking. Here, we integrate metabolic labeling and click chemistry technology with recombinant gp120 expression to demonstrate that gp120 glycans could be specifically labeled and directly detected. Selective labeling of gp120 by N-azidoacetylmannosamine (ManNAz) and N-azidoacetylgalactosamine (GalNAz) incorporation into the gp120 glycan shield was characterized by MS of tryptic glycopeptides. By using metabolically labeled gp120, we investigated the impact of gp120 glycosylation on its interaction with host cells and demonstrated that oligomannose enrichment and sialic acid deficiency drastically enhanced gp120 uptake by bone marrow–derived dendritic cells. Collectively, our data reveal an effective labeling and detection method for gp120, serving as a tool for functional characterization of the gp120 glycans and potentially other glycosylated proteins.